Sicily - Maupassant, Guy de, 1850-1893 (Italica historical travel guides., 2007)
"An English translation of Guy de Maupassant's description of his trip around Sicily and the neighboring islands in the Spring of 1885, with an introduction, notes and bibliography; illustrated with nineteenth-century engravings"--Provided by publisher